EXTRACTION KINETICS OF SAPPANG WOOD DYES (Caesalpinia sappan Linn) - Suryani - (PROSIDING SEMINAR KIMIA, 2015)
The development of food and beverage processing industry and the limited quantity and quality of natural dyes cause the use of synthetic dyes is increasing. The use of synthetic dyes can be replaced with natural dyes. One alternative that can be used natural dyes are dyes contained in Sappang wood (Caesalpinia sappan Linn.) For that conducted this research with the Ethanol Concentration and Temperature Effect to Extraction Sappang wood dye. The purpose of this study was to determine the effect of ethanol with various concentrations and temperatures as well as get the highest weight of the extract to the extraction of wood dye sappang.The research method used is the extraction of heat by using a set of equipment sokhlet. The treatments consisted of two variables, ethanol with various concentrations (70%, 80%, and 90%) and extraction temperature (60 0C, 70 0C, and 80oC).The results showed that the higher concentration of ethanol and the temperature the higher the percentage by weight of dry extract of Sappang wood dye produced. The highest extraction results obtained at a temperature of 80 ° C and the concentration of 90% by weight of dry extract yield the highest 0.7419 grams and percentages 9:27% and extraction kinetics is 3:24 10-3mol liter-1 s-1.